UJI POTENSI KULIT KOPI MENJADI BRIKET BIOARANG - , HARIS PURNAWAN, S.Pd.T, Dr. Ing. Ir. Kusnanto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The rate of economic growth and the increase of population has indirect impact on the increase of energy consumption that characterized by the depletion of energy resources, especially the consumption on non-renewable energy source, such as fossil fuel. Research on renewable energy source, as well as the alternative energy source, has been started manyyears ago as the need of new energy sources become an urgency. The purpose of research is to make charcoal briquettes based on raw coffe hulls material mixed with starch adhesives as an alternative energy source. In the process, itâs also find out the exact composition of charcoal and the adhesives, looking for an ideal pressure compression of the composition, and to determine the physical and chemical quality of briquette mold. Raw material for making charcoal briquettes in this study originated from the coffee hulls of solid waste coffee plantation. The briquette-making process begins with coffee pod waste pyrolysis in a reactor with a temperature of 400 Â°C, until the hulls become charcoal, which is marked by the cessation of liquid smoke from the smoke outlet